Maurice Gee's 'anti-Cartesian meditations': narcissism and relational trauma in Plumb. Issue 1 (2nd January 2020) - Drichel, Simone
ABSTRACT: In playfully positioning Descartes – recast as 'Des Cartes' – as 'a cousin of Les Miserables' in his best-known novel Plumb (1978), New Zealand writer Maurice Gee demonstrates that what lurks beneath Western culture's Cartesian heritage is a disavowed story of pain and misery. Reading the Cartesian cogito's withdrawal from the world as a narcissistic defence response to relational trauma, this article considers the relational damage that such a withdrawal causes. It argues that the ensuing cycle of intergenerational trauma can be broken only if the narcissistic ego reconnects with what Emmanuel Levinas calls the 'marvel of exteriority' – a reconnection that is predicated upon the ego's ability and willingness to tolerate the kind of vulnerability that Gee's solitary protagonist persistently disavows. What Gee's novel therefore offers us, in drawing attention to the 'misery' that may be both covered up and caused by such a disavowal of vulnerability, is a provocation to reconsider not just our contemporary cultural values of self-reliance, individualism, etc., but the Cartesian foundations upon which they are based.